Effectiveness of extrafine sngle inhaler triple therapy in Chronic Obstructive Pulmonary Disease (COPD) in Germany: the TriOptimize study - Geßner, Christian; Trinkmann, Frederik; Javan, Sanaz Bahari; Hövelmann, Raimund; Bogoevska, Valentina; Georges, George; Nudo, Elena; Criée, Carl-Peter (The International journal of chronic obstructive pulmonary disease, 2022)
Changes in HRQoL, COPD specific symptoms, lung function & treatment adherence after six months of treatment with efSITT in patients with moderate-to-severe COPD